PENGEMBANGAN PERANGKAT PEMBELAJARAN TEMATIK BERBASIS KARAKTER PADA KELAS IV SD - Faeza Rezi S (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2018)
Mutual respect and help others in learning are expected to improve students’ learning outcomes. The learning characteristics of elementary school thematic-integrative with scientific approach become challenges for teachers to develop learning activities that has to instilling noble values to the students. The purpose of this study is to develop the learning device that inserts the character values for the students through the learning activities. The type of this research is a Research and Development. The development model used is a four D Models that are: Define, Design, Develop and Disseminate. The subjects of this study are a teacher at SDN 03 Alai Padang, a teacher at SDN Percobaan Padang and IV.B grade students of SDN 03 Alai Padang. The finding of this Research and Development is a teacher’s handbook integrated with lesson plans and student learning books. The findings can be used in learning process to improve students' cooperative skills, instilling character values and improving students' learning outcomes.Keyword: Thematic Education, Character building.